Investigating the structural impact of hiv-1 integrase natural occurring polymorphisms and novel mutations identified among group m subtypes circulating in sub-Saharan Africa - Mikasi, Sello Given (Stellenbosch : Stellenbosch University, 2020)
Thesis (DScMedSc)--Stellenbosch University, 2020.